Dividend Policy Determination And Company Performance: Management Ownership And Financial Performance (Financial Management Literature Review) - Zuriah sholda, Hera; Rimbano, Dheo; Dila faramitha, Tasya; Ratnasari, Yesi; Mawaddah, Shinta; Indah sari, Maya Nur; Aprilia , Risma Dwi; Ramadhan , M Iqbal; Lingga, Gandi putra; akbar, Raja anan; Dona, Rama (ADPEBI, 2022)
Previous research or relevant research is very important in a research or scientific article. This article reviews the effect of dividend policy and company performance on companies listed on the Indonesian stock exchange. The results of this literature review article are: 1) Dividend Policy has a Positive and Significant Impact on Company Performance; 2) Dividend Policy Has a Positive and Significant Impact on Company Performance. 3) Financial Performance Has a Positive and Significant Impact on Company Performance 4) Managerial Ownership Has a Positive and Significant Impact on Dividend Policy. 5) Financial Performance Has a Positive and Significant Effect on Managerial Ownership. Dividend policy is a decision in determining the optimal proportion of profit between the distribution of profits as dividends and retained earnings.